Combined Use of Pyelolithotomy and Endoscopy: An Alternative Surgical Treatment for Staghorn Urolithiasis in Children - Jurkiewicz, Beata; Zabkowski, Tomasz; Jobs, Katarzyna; Samotyjek, Joanna; Jung, Anna (Urology Journal, 2016)
Purpose: To present a combining pyelolithotomy and endoscopy, an alternative approach for treating staghorn calculi in children. Materials and Methods: We treated 1414 children (age, 10 months to 17 years) with urolithiasis between 2009 and 2013 in the Pediatric Surgery Department and in the Pediatrics and Nephrology Department, Military Institute of Medicine in Warsaw. Most patients were treated conservatively. In 162 cases, an extracorporeal shockwave lithotripsy (SWL) procedure was needed. Surgery was only used in patients who had failed SWL. We performed minimally invasive procedures, ureterolithotripsy using semi-rigid and flexible ureterorenoscopes or percutaneous nephrolithotomy (PCNL) in 126 patients. Results: In the most serious cases of staghorn or multifocal calculi, we performed a combined operation of pyelolithotomy with endoscopic removal of concrements from all calyces of the diseased kidney. In 15 out of the 18 combination treatments (83.3%), concrements were completely removed from the kidney in a single procedure. In three cases, fine concrements (5 to 6 mm) remained after the procedure, and these were candidate for SWL. In one case, a boy aged 4 years, symptoms of infection in the urinary tract occurred 2 days after the procedure. Conclusion: Combining pyelolithotomy with endoscopy to remove concrements clears the diseased kidney without causing parenchymal damage in one procedure. The method is safe in children, does not require blood transfusion, and helps maintain kidney function.